Beyond the Polis: Rituals, Rites, and Cults in Early and Archaic Greece (12th–6th Centuries BC) - Fowler, Michael Anthony (Kernos, 2021)
The co-edited volume under consideration presents the peer-reviewed proceedings of a homonymous conference held at the Free University of Brussels and the Royal Academy of Belgium in 2015. It opens with a general introduction by the editors to the topic of the conference and to its 17 constitutive papers. The contributions deal with ceremonial contexts and rituals of diverse kinds, which antedate, transcend, or develop beneath or independently of the polis and its institutions. The papers are...